2019
DOI: 10.1111/ejh.13248
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell mobilization following PD‐1 blockade: Cytokine release syndrome after transplantation managed with ascorbic acid

Abstract: Patients with recurrent/refractory (R/R) classical Hodgkin's Lymphoma (cHL) have poor survival with conventional therapy.In these patients, autologous hematopoietic stem cell transplant (SCT) is the most commonly employed salvage therapy. 1 Immune checkpoint inhibitors also have significant activity in recurrent HL. 2 Program death-1 (PD-1) is a crucial pathway in immune tolerance. Nivolumab is a PD-1 antagonist that was the first approved checkpoint inhibitor in hematological malignancies including HL.PD-1 bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In addition, if penetration into the brain is desired, small molecules can be effective (7,8). Second, there are rare but severe immune-related side effects of checkpoint inhibition that require immediate drug discontinuation (9)(10)(11)(12). Since mAbs have long half-lives in the body (typically weeks) (13), the treatment of such severe immunerelated side effects is primarily supportive.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, if penetration into the brain is desired, small molecules can be effective (7,8). Second, there are rare but severe immune-related side effects of checkpoint inhibition that require immediate drug discontinuation (9)(10)(11)(12). Since mAbs have long half-lives in the body (typically weeks) (13), the treatment of such severe immunerelated side effects is primarily supportive.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, an additional seven papers were excluded upon closer inspection, as they pertained to hemophagocytic lymphohistiocytosis, capillary-leak syndrome, or anti-CD19 chimeric antigen receptor (CAR) T-cell therapy. In total, we accurately summarized 22 papers [ [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] ]. A total of 49 patients were enrolled.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Checkpoint inhibition has notably shown one of the most significant adverse effects in CAR-T immunotherapies [31]. The most current CRS data from current CAR-T cell and blinatu-momab studies in hematologic malignancies reported that CRS occurred in frequencies of up to 100% in CD19-targeted CAR T cell trials [32,33].…”
Section: Pd-1 Blockade With Different Immune Checkpoint Inhibitorsmentioning
confidence: 99%